Exploring the influence of export orientation on small firms performance: the moderating role of export knowledge - Abdul Rahim, Norhuda; Abubakar, Mukhtar Salisu; Yahya, Mohamed Hisham; Raja Yusof, Raja Nerina (China University of Mining and Technology, 2024)
Despite the burgeoning studies on the performance implications of expo1i orientation and export knowledge, our comprehension of how they influence the export performance of SMEs is scarce. This study aims to assess the impact of export orientation on SME export performance in Nigeria through the moderating effect of export knowledge. The research model was evaluated with a sample of 278 Nigerian exporting SMEs using a convenience sampling technique, and a questionnaire was applied for data collection. Partial least square-structural equation modelling (PLS-SEM) was employed. The conclusion of the analysis supports the notion that export orientation improves SMEs' export performance in Nigeria. Moreover, export knowledge was found to moderate the association significantly. This finding provides practical insights for industry players on the variables that drive the export performance of SMEs.